Allergen‐loaded strontium‐doped hydroxyapatite spheres improve allergen‐specific immunotherapy in mice. Issue 4 (22nd December 2016) - Garbani, M.; Xia, W.; Rhyner, C.; Prati, M.; Scheynius, A.; Malissen, B.; Engqvist, H.; Maurer, M.; Crameri, R.; Terhorst, D.
Abstract: Background: Immunomodulatory interventions play a key role in the treatment of infections and cancer as well as allergic diseases. Adjuvants such as micro‐ and nanoparticles are often added to immunomodulatory therapies to enhance the triggered immune response. Here, we report the immunological assessment of novel and economically manufactured microparticle adjuvants, namely strontium‐doped hydroxyapatite porous spheres (SHAS), which we suggest for the use as adjuvant and carrier in allergen‐specific immunotherapy (ASIT). Methods and results: Scanning electron microscopy revealed that the synthesis procedure developed for the production of SHAS results in a highly homogeneous population of spheres. Strontium‐doped hydroxyapatite porous spheres bound and released proteins such as ovalbumin (OVA) or the major cat allergen Fel d 1. SHAS‐OVA were taken up by human monocyte‐derived dendritic cells (mdDCs) and murine DCs and did not have any necrotic or apoptotic effects even at high densities. In a murine model of ASIT for allergic asthmatic inflammation, we found that OVA released from subcutaneously injected SHAS‐OVA led to a sustained stimulation of both CD4 + and CD8 + T cells. Allergen‐specific immunotherapy with SHAS‐OVA as compared to soluble OVA resulted in similar humoral responses but in a higher efficacy as assessed by symptom scoring. Conclusion: We conclude that SHAS may constitute a suitable carrier and adjuvant for ASIT with great potential due to its unique protein‐binding properties.